Controllable supramolecular self-assemblies (rods–wires–spheres) and ICT/PET based perylene probes for palladium detection in solution and the solid state. (14th December 2017) - Kumar, Kapil; Bhargava, Gaurav; Kumar, Subodh; Singh, Prabhpreet
Abstract : AC-PDI shows solvent dependent self-assembly into nanowires, rods and spheres. It could be used for detection of Pd 0 in 50% HEPES buffer–DMSO (39 nM, UV-Vis; 45 nM, fluorescence) and the solid state (0.58 pg cm −2 ). Abstract : Control over the self-assembly of bay functionalized perylene diimides and the response of these self-assembled materials towards analytes in mixed aqueous–organic media is important to consider the potential of this intriguing dye family in supramolecular chemistry. Herein, we have designed and synthesized allylcarbonate-functionalized perylene diimideAC-PDI which shows solvent dependent supramolecular nanostructures and could readily self-assemble into nanorods of tens of μm in length in CH3 CN, but the length of the rods drammatically decreased to 0.8–1.2 μm in a H2 O : CH3 CN (1 : 1, v/v) mixture. Interestingly, AC-PDI self-assembles into nanowires of several tens of μm in length in a 30% H2 O:DMSO mixture and forms only nanospheres in ethyl acetate.AC-PDI can be used as a near-infrared (NIR) colorimetric ( λ abs 685 nm) and fluorescent ( λ em 530/570 nm) probe for selective detection of Pd 0 [LOD = 39 nM (UV); 45 nM (FI)]. Furthemore, TLC strips coated with theAC-PDI probe could detect 0.58 pg cm −2 of Pd 0 in the solid state. The mechanism of interaction ofAC-PDI with Pd 0 has been confirmed by 1 H NMR titration, kinetic and morphological studies.